2002
DOI: 10.1046/j.1364-3703.2002.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea mosaic virus: effects on host cell processes

Abstract: SUMMARYTaxonomy: Cowpea mosaic virus (CPMV) is the type member of the Comoviridae and bears a strong resemblance to animal picornaviruses, both in gene organization and in the amino acid sequence of replication proteins. Little systematic work has been done to compare isolates of the virus from different parts of the world.Physical properties: Purified preparations of virus contain three centrifugal components; empty protein shells without RNA (T) and two nucleoprotein components (M and B), containing 24% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 53 publications
0
19
0
5
Order By: Relevance
“…; 4 h after embedding), MP-GFP had clearly accumulated in peripheral punctate spots of various sizes and in tubules, as observed previously (Gopinath et al, 2003). Since CPMV RNA2 is translated into two overlapping polyproteins due to the presence of two in-frame start codons (Pouwels et al, 2002a), GFP is also fused to the cofactor for RNA2 replication, which causes fluorescence to accumulate in the nucleus as well (Gopinath et al, 2000;Kasteel et al, 1993;Pouwels et al, 2002b). During the course of the experiment, at the site of some, mostly small, peripheral punctate spots, a tubule was formed ( Fig.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…; 4 h after embedding), MP-GFP had clearly accumulated in peripheral punctate spots of various sizes and in tubules, as observed previously (Gopinath et al, 2003). Since CPMV RNA2 is translated into two overlapping polyproteins due to the presence of two in-frame start codons (Pouwels et al, 2002a), GFP is also fused to the cofactor for RNA2 replication, which causes fluorescence to accumulate in the nucleus as well (Gopinath et al, 2000;Kasteel et al, 1993;Pouwels et al, 2002b). During the course of the experiment, at the site of some, mostly small, peripheral punctate spots, a tubule was formed ( Fig.…”
Section: Resultsmentioning
confidence: 58%
“…To determine whether larger proteins could also be accommodated in the plasma membrane around tubules, a construct encoding a fusion between YFP-Zm7hvr and the 110 kDa protein, encoded by CPMV RNA1 (Pouwels et al, 2002a), was used (pMON-110-YFP-Zm7hvr). Protoplasts inoculated with pMON-110-YFP-Zm7hvr revealed that 110-YFP-Zm7hvr also accumulated in the plasma membrane (Fig.…”
Section: Mp Molecules Interact Within the Tubulementioning
confidence: 99%
See 2 more Smart Citations
“…1), these viruses share many common features. In addition to having characteristics in common with other picornavirales as discussed above (general capsid structure, polyprotein strategy for [28,30,33,34,43]. In the case of comoviruses, nepoviruses and cheraviruses, experimental evidence has been provided indicating that the tubular structures enable cell-to-cell movement of the virus in the plant and that the viral movement protein is a structural component of the tubules [31,32,46,48,49].…”
Section: Rationale For the Creation Of The Proposed Family Secoviridaementioning
confidence: 99%